2002
DOI: 10.1046/j.1471-0528.2002.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

The Klippel–Trenaunay syndrome in pregnancy

Abstract: Case reportA 21 year old primipara was referred to our unit for advice regarding mode of delivery. The woman was 38 weeks pregnant and had an oblique lie. Her pregnancy had been uncomplicated. However, she had a large congenital haemangioma of the left buttock and thigh ( Fig. 1) extending to the lower leg and foot. There was a macular telangiectatic haemangioma that was associated with lateral venous varicosities that had developed over the past few years and had become worse in pregnancy. Both lower limbs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
(11 reference statements)
0
9
1
Order By: Relevance
“…(7,16,17) Severe complications such as paraplegia and uterine prolapse were reported in case studies, (8,9) but were not found in our study. In addition, our data is in contradiction with current literature on pregnancy outcomes in KTS patients.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…(7,16,17) Severe complications such as paraplegia and uterine prolapse were reported in case studies, (8,9) but were not found in our study. In addition, our data is in contradiction with current literature on pregnancy outcomes in KTS patients.…”
Section: Discussioncontrasting
confidence: 47%
“…The largest case series published in the literature so far consisted of 4 patients. (6) Severe pregnancy complications in this patient category have previously been described in case reports and case series, (7,16,17) but these findings could have been coincidental considering the small sample sizes. This study, enrolling a large proportion of women with KTS in the Netherlands, provides stronger evidence to confirm the high prevalence of these complications.…”
Section: Strengths and Limitationsmentioning
confidence: 76%
“…4 The morbidity experienced includes bleeding, pain, infection, and negative self-body image. 25,37,38 Treatment usually consists of combination surgery and sclerotherapy with aspirin to minimize the pain associated with phlebothrombosis and prophylactic antibiotics to prevent recurrent infections. 25,37,38 Treatment usually consists of combination surgery and sclerotherapy with aspirin to minimize the pain associated with phlebothrombosis and prophylactic antibiotics to prevent recurrent infections.…”
Section: Discussionmentioning
confidence: 99%
“…Another case was reported with a fetal death from signifi cant maternal bleeding from the varix rupture, with the bleeding spot seen as a hole in a localized varicosity of a vein [7]. Watermeyer et al [8] reported a 21-year-old primiparous woman with a massive plexus of varicosities fi lling the uterovesical fold that extended over the lower uterine segment and performed a classical Cesarean section with a blood loss of 1,500 mL. This patient experienced spontaneous vaginal bleeding after coughing infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize the possibility of associated anatomical or pathological diseases. It may include leg varices, venous malformation of the labia, clitorial area, or vagina with or without arteriovenous malformation on the limbs or trunk (KlippelTrenaunay syndrome) [8]. The Klippel-Trenaunay syndrome consists of a triad of cutaneous port-wine capillary malformations, varicose veins and hemihypertrophy of soft tissue and bone.…”
Section: Discussionmentioning
confidence: 99%